Fresh Pork and Porcine Reproductive and Respiratory Syndrome Virus: Factors Related to the Risk of Disease Transmission. Issue 4 (10th September 2013) - Hall, W.; Neumann, E.
Summary Porcine reproductive and respiratory syndrome virus (PRRS) is a highly infectious virus. Experimentally, the disease can be induced in naïve pigs by the oral, intranasal and intramuscular routes. Depending on the virulence of the strain of the virus and the age of the pig, peak viremia can occur within 7 days of infection, and live virus can be isolated from blood or lymph nodes for several months post‐infection. Young pigs tend to develop higher titres of viremia than older pigs infected by the same route and dose with the same strain of virus. Porcine reproductive and respiratory syndrome virus survives in pork harvested from infected pigs for extended periods at temperatures of −20 or −70°C. In experimentally infected pigs, survival of PRRS virus in muscle held at 4°C has been demonstrated for at least 7 days, and infectivity of the virus in these samples was confirmed by bioassay. The optimal pH range for the survival of PRRS virus is thought to be 6.0 to 7.5. The elevated pH of non‐meat tissues (generally one pH unit higher) is likely to favour extended survival of PRRS virus in pig carcasses from which all superficial and deep lymph nodes have not been removed. It is likely that exsanguinated carcasses held at 4°C retain sufficient blood or lymph tissue to contain infective doses of PRRS virus. Porcine reproductive and respiratory syndrome virus is rapidly inactivated by heat, providing a predictable method to ensure that pork tissues are free of viable virus and feeding of cooked swill or garbage should not constitute a risk to pigs. While the probability of viable PRRS virus being present in a pig carcass may be low, the risk is not zero. The importation of raw pork into countries where PRRS is not endemic represents a hazard with potentially severe economic consequences.